Thermal Field Laws of the Permafrost in the Vorkuta Region (Zakonomernosti Temperaturnogo Polya Vechnoi Merzloty na Vorkute) - Redozubov,D. B. (1954)
The work presented here consists of two basic chapters. The first chapter expounds those thermal field laws in permafrost bodies which are general for the permafrost region as a whole. The second chapter discusses the thermal field laws which are characteristic of the permafrost in the Vorkuta region. (Author) Trans. from Akademiya Nauk SSSR. Institut Merzlotovedeniya. Trudy, v1 1946, by Leonid Stambul-Sheik, and Jaroslav Jan Peel.